Connexin diversity in the heart: insights from transgenic mouse models - Verheule, Sander; Kaese, Sven (Frontiers in Pharmacology, 2013)
Cardiac conduction is mediated by gap junction channels that are formed by connexin (Cx) protein subunits. The connexin family of proteins consists of 24 members, varying in their biophysical properties and ability to combine with other connexins into heteromeric gap junction channels. The mammalian heart shows regional differences both in connexin expression profile and in degree of electrical coupling. The latter reflects functional requirements for conduction velocity, which needs to be low in the sinoatrial and atrioventricular nodes and high in the ventricular conduction system. Over the past 20 years, knowledge of the biology of gap junction channels and their role in the genesis of cardiac arrhythmias has increased enormously. This review focuses on the insights gained from transgenic mouse models. The mouse heart expresses Cx30, 30.2, 37, 40, 43, 45 and 46. For these connexins, a variety of knock-outs, heart-specific knock-outs, conditional knock-outs, double knock-outs, knock-ins and overexpressers has been studied. We discuss the cardiac phenotype in these models and compare Cx expression between mice and men. Mouse models have enhanced our understanding of (patho)-physiological implications of Cx diversity in the heart. In principle, connexin-specific modulation of electrical coupling in the heart represents an interesting treatment strategy for cardiac arrhythmias and conduction disorders.